1996
DOI: 10.1111/j.1442-200x.1996.tb03724.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of aplastic anemia with antithymocyte globulin, cyclosporin A, methylprednisolone, danazole and recombinant human granulocyte‐colony stimulating factor

Abstract: The main purpose of the present study was to determine the response rate to immunosuppressive therapy combined with recombinant human granulocyte‐colony stimulating factor (rhG‐CSF) and its efficacy for preventing infections in patients with severe aplastic anemia. The treatments included one course of antithymocyte globulin, cyclosporin A, methylprednisolone, danazole and rhG‐CSF. Three patients had very severe aplastic anemia and two had moderate aplastic anemia. One patient relapsed 13 months following the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…for 6 months, with dose adjustment to maintain a serum trough concentration of 100-200 ng/ml), and danazol (5 mg/kg p.o. for 6 months) [15]. No adverse effects were observed except for transient Coombs' positive hemolysis, which recovered without specific treatment.…”
Section: Detection Of the B19 Virus Antigen And Genomementioning
confidence: 87%
“…for 6 months, with dose adjustment to maintain a serum trough concentration of 100-200 ng/ml), and danazol (5 mg/kg p.o. for 6 months) [15]. No adverse effects were observed except for transient Coombs' positive hemolysis, which recovered without specific treatment.…”
Section: Detection Of the B19 Virus Antigen And Genomementioning
confidence: 87%
“…Danazol, a synthetic attenuated androgen, has been used widely for anemia in variety of disorders, including pure red cell aplasia, autoimmune hemolytic anemia, aplastic anemia, and IMF [9][10][11][12][13][14]. Cervantes et al [15] reported 30 IMF patients who took danazol for 20.5 months and 11 patients (37%) achieved complete remission (transfusion cessation with normal hemoglobin level).…”
Section: Discussionmentioning
confidence: 99%
“…CYA and antithymocyte globulin (ATG) are thought to inhibit the functioning of the T‐cells that suppress stem cells [10]. Immunosuppressive therapy with G‐CSF for the treatment of aplastic anemia was reported by Bacigalupo et al [16] and by Shichino et al [17]. Furthermore, high‐dose G‐CSF therapy [18] and combination therapy with G‐CSF and rhEPO [19] are advocated for the successful treatment of severe aplastic anemia.…”
Section: Discussionmentioning
confidence: 99%